Pengaruh Model Project-Based Learning Terintegrasi STEM terhadap Kemampuan Pemecahan Masalah Siswa pada Pembelajaran IPA di MTs - Moammar Qadafi (Alpatih Harapan Semesta, 2026)
Problem-solving skills are one of the 21st-century skills that need to be developed through innovative and learner-centred education. The 2013 Curriculum emphasises the application of learning models that encourage active student engagement, one of which is through Project-Based Learning (PjBL). However, observations at MTs Negeri 4 Lombok Timur indicate that the implementation of Project-Based Learning (PjBL) is not yet optimal and the integration of the Science, Technology, Engineering, and Mathematics (STEM) approach in learning is still limited, resulting in low problem-solving abilities among students. This study aims to analyse the influence of the Project-Based Learning (PjBL) model integrated with STEM on students' problem-solving abilities. The research uses a quasi-experimental method with a posttest-only control group design. The research sample consists of an experimental class that receives STEM-integrated PjBL learning and a control class that receives conventional learning. Data on problem-solving ability were collected through essay tests and observation sheets. Data analysis was conducted through normality tests, homogeneity tests, and hypothesis testing using the t-test. The research results showed that the data were normally and homogeneously distributed. The hypothesis test indicated a significance value of less than 0.05, which indicates a significant difference between the experimental class and the control class. Thus, the STEM-integrated PjBL model has proven effective in enhancing students' problem-solving abilities in science learning. These findings imply that the integration of STEM in PjBL can serve as an innovative learning alternative to improve the quality of 21st-century education.